2014
DOI: 10.1111/cod.12270
|View full text |Cite
|
Sign up to set email alerts
|

Epicutaneous exposure to nickel induces nickel allergy in mice via a MyD88‐dependent and interleukin‐1‐dependent pathway

Abstract: This new model for nickel allergy that reflects epicutaneous exposure to nickel in humans shows that nickel allergy is dependent on MyD88 and IL-1 receptor signalling, but independent of TLR4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 49 publications
1
26
0
2
Order By: Relevance
“…Both nickel and cobalt facilitate dimerization of human TLR4, thereby inducing the production of various cytokines and chemokines required for initiation of the allergic response . Furthermore, we have shown that nickel allergy can be induced in mice via an MyD88‐dependent and IL‐1‐dependent but TLR4‐independent pathway, indicating that nickel can activate the innate immune response by various mechanisms . In agreement with this, it has been shown that NiCl 2 induces NLRP3–ASC–capase‐1 inflammasome activation in APCs, resulting in IL‐1β production via mechanisms involving lysosome rupture, mitochondrial ROS, generation and cation flux .…”
Section: Effects Of Mixing Contact Allergenssupporting
confidence: 72%
See 1 more Smart Citation
“…Both nickel and cobalt facilitate dimerization of human TLR4, thereby inducing the production of various cytokines and chemokines required for initiation of the allergic response . Furthermore, we have shown that nickel allergy can be induced in mice via an MyD88‐dependent and IL‐1‐dependent but TLR4‐independent pathway, indicating that nickel can activate the innate immune response by various mechanisms . In agreement with this, it has been shown that NiCl 2 induces NLRP3–ASC–capase‐1 inflammasome activation in APCs, resulting in IL‐1β production via mechanisms involving lysosome rupture, mitochondrial ROS, generation and cation flux .…”
Section: Effects Of Mixing Contact Allergenssupporting
confidence: 72%
“…Contact allergens can also lead to activation of the NLRP3 inflammasome, which activates caspase‐1, leading to processing of pro‐interleukin (IL)‐1β and pro‐IL‐18 to IL‐1β and IL‐18, respectively . IL1β is already induced in the skin 15 min after exposure to allergens, and plays a central role in the allergic response . Activation of the NLRP3 inflammasome by contact allergens seems to be mediated by an indirect pathway involving reactive oxygen species (ROS) and ATP .…”
Section: Immune Responses To Contact Allergens In Generalmentioning
confidence: 99%
“…However, it is not known whether these metals activate ROS/NLRP3 inflammasomes in vivo or whether this pathway is required for the generation of hypersensitivity. While IL-1R signaling has been shown to be important in murine models of nickel-induced hypersensitivity [20], release of biologically-active IL-1α is not dependent upon the inflammasome and could account for these effects [21]. For example, beryllium exposure in the lung induced rapid release of IL-1α and not IL-1β; however, after long-term exposure to beryllium, IL-1β is released [22,23].…”
Section: Recognition Of Metals By the Innate Immune Systemmentioning
confidence: 99%
“…Mice were sensitized with 10% NiCl 2 , 10% NiCl 2 plus 1% CoCl 2 , 10% CoCl 2 , 10% CoCl 2 plus 1% NiCl 2 in white petrolatum or vehicle (pure white petrolatum) as previously described (Fig. 1a) (9). Mice studies were performed in accordance with Danish national animal protection guidelines 3 weeks after sensitization, the mice were challenged by painting with 10% NiCl 2 , 10% CoCl 2 or vehicle (pure white petrolatum) twice with a 24-h interval.…”
Section: Experimental Designmentioning
confidence: 99%